Effectiveness of Variations in Silica Sand and Activated Carbon Filter Media in Reducing Iron (Fe) Levels in Well Water - Yulian Gilang Prayoga; Windi Wulandari (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Water sources as a basic human need can affect human health, so they must meet the established clean water quality standards. Therefore, the air source used by humans must be guaranteed and protected from metal ions such as manganese (Mn) and iron (Fe) which are excessive for the body. This research aims to determine the effectiveness of variations in filter media arrangements from a combination of silica sand filters and activated carbon to reduce iron (Fe) levels in well water. The method used is quasi experimental with pre-test and post-test. This research was carried out in Balesari, Sukoharjo from October 2023 to March 2024 with the population of this study consisting of 1 community well water which has high levels of iron (Fe). This research uses a quota sampling technique. The instrument used in this research was a laboratory test for iron (Fe) levels. Analysis was carried out using the Anova test and paired T test. This research uses data analysis based on the use of software in the form of the SPSS application. The results of statistical processing carried out on filter media (I) show that the sig value is 0.002. The filter media (II) and (III) show that the sig value is 0.000. This shows that the significance of the three variations in the filter media arrangement of the combination of silica sand and activated carbon has a sig p value ≤ 0.05, so there is a difference in the reduction in iron (Fe) content before and after treatment from the variation in the filter media arrangement of the combination of silica sand and activated carbon for reduce iron (Fe) content in well water. Conclusion, variations in silica sand and activated carbon filter media are effective in reducing iron (Fe) levels in well water in Balesari Sukoharjo. Suggestions for future researchers include the need for additional media that can absorb dissolved iron content, and the need to add appropriate media so that the filtration process runs optimally.Keywords: Activated carbon, Iron content, Salica sand